Changes in Pain Modulation Occur Soon After Whiplash Trauma but are not Related to Altered Perception of Distorted Visual Feedback. Issue 7 (30th September 2013) - Daenen, Liesbeth; Nijs, Jo; Cras, Patrick; Wouters, Kristien; Roussel, Nathalie
Abstract Objectives Widespread sensory hypersensitivity has been observed in acute whiplash associated disorders (WAD). Changes in descending pain modulation take part in central sensitization. However, endogenous pain modulation has never been investigated in acute WAD. Altered perception of distorted visual feedback has been observed in WAD. Both mechanisms (ie, pain modulation and perception of distorted visual feedback) may be different components of one integrated system orchestrated by the brain. This study evaluated conditioned pain modulation (CPM) in acute WAD. Secondly, we investigated whether changes in CPM are associated with altered perception of distorted visual feedback. Methods Thirty patients with acute WAD, 35 patients with chronic WAD and 31 controls were subjected to an experiment evaluating CPM and a coordination task inducing visual mediated changes between sensory feedback and motor output. Results A significant CPM effect was observed in acute WAD (P = 0.012 and P = 0.006), which was significantly lower compared to controls (P = 0.004 and P = 0.020). No obvious differences in CPM were found between acute and chronic WAD (P = 0.098 and P = 0.041). Changes in CPM were unrelated to altered perception of distorted visual feedback (P > 0.01). Conclusion Changes in CPM were observed in acute WAD, suggesting less efficient pain modulation. The results suggest that central pain and sensorimotor processing underlie distinctive mechanisms.